Over a million students use our free study notes to help them with their homework
>>> 2x+5=3x^2 >>> 3x^2-2x-5=0>>> (3x-5)(x+1)=0>>> x=-1 or x=5/3>>> therefore (-1,3) and (5/3,25/3)
=(x-4)2(x-4)=(x2-8x+16)(x-4)=x3-4x2-8x2+32x+16x-64= x3-12x2+48x-64
First, use the trigonometric identity tan(x) = sin(x) / cos(x) to rewrite the function. It should now be very apparent that f(x) is now actually a ratio of two functions, and therefore the quotient rule w...
This tests the students knowledge of differentiation rules as well as algebraic manipulation. Namely the product rule and implicit differentiation. Differentiate term by term and then isolate dy/dx using ...
In the form (x-x1)^2+(y-y1)^2=r^2Hence equation is: (x-2)^2+(y-9)^2=16
←
245
246
247
248
249
→
Internet Safety
Payment Security
Cyber
Essentials